2017
DOI: 10.1371/journal.pone.0171263
|View full text |Cite
|
Sign up to set email alerts
|

Robust network topologies for generating oscillations with temperature-independent periods

Abstract: Nearly all living systems feature a temperature-independent oscillation period in circadian clocks. This ubiquitous property occurs at the system level and is rooted in the network architecture of the clock machinery. To investigate the mechanism of this prominent property of the circadian clock and provide general guidance for generating robust genetic oscillators with temperature-compensated oscillations, we theoretically explored the design principle and core network topologies preferred by oscillations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…The authors concluded that temperature compensation is likely determined by a rate-limiting process(es) that are temperature sensitive, consistent with the phosphoswitch mechanism ( 43 ). Another mathematical model for temperature compensation has recently proposed a temperature insulation mechanism where oscillation period is determined by very few temperature-independent or only slightly temperature-dependent parameters, but where other parameters remain strongly temperature dependent ( 44 ). This model is analogous to the proposed phosphoswitch mechanism in which the CK1ε/δ is temperature independent or slightly dependent, whereas the priming kinase is temperature dependent ( 38 ).…”
Section: Period2 Phosphoswitch Unravels the Mechanism Of Temperature mentioning
confidence: 99%
“…The authors concluded that temperature compensation is likely determined by a rate-limiting process(es) that are temperature sensitive, consistent with the phosphoswitch mechanism ( 43 ). Another mathematical model for temperature compensation has recently proposed a temperature insulation mechanism where oscillation period is determined by very few temperature-independent or only slightly temperature-dependent parameters, but where other parameters remain strongly temperature dependent ( 44 ). This model is analogous to the proposed phosphoswitch mechanism in which the CK1ε/δ is temperature independent or slightly dependent, whereas the priming kinase is temperature dependent ( 38 ).…”
Section: Period2 Phosphoswitch Unravels the Mechanism Of Temperature mentioning
confidence: 99%
“…The Repressilator (Figure 10Ai), when coupled, has long been proposed for use in modeling simplified clock networks (Hinze et al, 2011). Significantly, the Repressilator also repeatedly emerges as a core motif from analyses of real circadian clock networks ( Wu et al, 2017). In 2011, Ukai-Tadenuma et al, using a minimal-network representation of the mammalian clock, found delayed negative feedback and Repressilator motifs at its core.…”
Section: Oscillator Structure In Circadian and Synthetic Clocksmentioning
confidence: 99%
“…A classic example is that of the circadian clock which oscillates according to the day-night cycle [52,53]. In mammals a set of three genes, cryptochrome (Cry), period (Per), and Rev-erb serve as a major core element of the circadian network [54]. A repressilator is responsible for controlling circadian timing in A. thaliana Synthetic circuits built from well-characterized genetic parts can also exhibit oscillations [55,56].…”
Section: Repressilatormentioning
confidence: 99%